Driver Drowsiness Detection for Safety Assistance - Mohd Rizwan Tahoor, M.A Jawad, Abdul Jabbar, Mohammed Abdul Bari (Mathematical Statistician and Engineering Applications, 2023)
Driver fatigue is one of the major causes of collisions and incidents globally. Identifying the driver’s fatigue is one of the most dependable ways to assess their level of exhaustion. The creation of a functional prototype for a drowsiness detection method is the aim of this work. This gadget watches a driver’s face and triggers an alarm if it detects signs of fatigue. The application is a superb, unobtrusive tracking system. The goal is to enhance the driver’s comfort without becoming overbearing. This study records the eye blink of the driver. An alert is triggered and the driver is deemed sleepy if their eyes remain shut for an endless period of time. OpenCV is currently configured to recognize face traits was used to the model for facial location detection.